Extinguishment of hydrocarbon pool fires by ultrafine water mist with ammonium/amidogen compound in an improved cup burner. (21st June 2018) - Liang, Tianshui; Li, Runwan; Li, Jing; Xu, Yanyan; Zhong, Wei; Zhao, Jun; Lo, Siuming
Summary: Ultrafine water mist (UFWM) (<10 μm), as a total flooding agent, has been proven to overcome obstructions in extinguishing fire. To examine the efficacy of UFWM extinguishing pool fires and reveal the primary fire extinguishing mechanisms of heat adsorption, a predictive model of minimum extinguishing concentration (MEC) is developed based on heat extraction, and the experimental data of MECs were obtained with an improved cup burner. The contribution of heat adsorption is about 25% to 50%, and turbulence effect also plays an important role in extinguishing fire. To improve fire inhibition effectiveness of UFWM by turbulence effect, CO (NH2 )2, NH4 HCO3, and (NH4 )2 HPO4 were selected as additives; KCl and KH2 PO4 were also chosen for comparison purpose. It is discovered that CO (NH2 )2 and (NH4 )2 HPO4 in the low concentrations can improve the fire extinction effectiveness except NH4 HCO3 . CO (NH2 )2 has the most contribution to fire extinction at the optimum concentration (about 0.01 mol L −1 for n‐heptane fire and 0.03 mol L −1 for ethanol fire). Moreover, CO (NH2 )2 (at 0.03 mol L −1 ) was dramatically better than KH2 PO4 in extinguishing ethanol fire, and its effect is very close to that of KCl (at 0.067 mol L −1 ) for ethanol fire.